3-Dimensional construction of the modularized rail structure in various posture conditions. (17th December 2022) - Yokomura, Ryota; Warisawa, Shin'ichi; Fukui, Rui
Abstract : Our research group has been developing an automated modularized rail structure construction system. Our system provides robot's locomotion and operational infrastructure in hazardous environments where manned work is difficult. In previous studies, various modules and robots have been developed, and stable transfer of modules between robots in multiple postures has been achieved. However, 3-D construction is not yet realized. In this study, the relationship between the contact force and posture of the constructor robot's (C-robot) end-effector is estimated through force balance calculation and deformation analysis is performed based on the finite element method. The results of construction experiment showed that pushing motion and improvement of the stiffness of the C-robot's grasping part increase the success rate of module construction in the vertically downward direction, which is the most difficult condition. Finally, this study proved that 3-D construction of a modularized rail structure is feasible in various posture condition. GRAPHICAL ABSTRACT: UF0001